Where is the missing value? Evidence from the game industry IPOs underpricing in Poland - Paweł Śliwiński; Szymon Ablewski; Kamil Gemra; Michał Łukowski (International Journal of Management and Economics, 2022)
The underpricing phenomenon on financial markets has long been the research subject in many financial areas - from neoclassical to behavioral finance. Once confirmed as a persistent pattern, it has begun an ongoing discussion as to its possible causes. Our study examined the phenomenon of IPO underpricing for companies from the game sector in Poland from 2016 to 2020. Many IPOs in Poland have attracted both international companies and investors, making the Warsaw Stock Exchange a kind of financial hub for game companies. Analyzing the whole IPO market in Poland, we however found substantial IPO underpricing, which is statistically higher in the game sector than in the no-game group of debuting companies. Our research argues that the issuer's industry may influence the size of the IPO's first-day return. We also noticed that the way the IPO was carried out influenced the underpricing. Greater underpricing characterized private offers compared to public offers.
Keywords: G41; G11; G12; 650; behavioral biases; game industry; IPO underpricing